Occurrence of mugilid and sparid fishes in Zostera capensis and bare sediment habitats of the Knysna Estuary - Pollard, Melissa (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2018)
Seagrass meadows are regarded as one of the most unique and valuable ecosystems in the biosphere, primarily because of the variety of services that they provide. Seagrass meadows serve as nursery grounds for many species and often play an important role in the juvenile stages of economically and recreationally important fish. Zostera capensis Setchell is one of the most dominant submerged macrophytes and the most common seagrass in South African estuaries and is often referred to as eelgrass. Zostera capensis meadows occupy a large area within the Knysna Estuary but little is known about their importance to associated fish assemblages. With Z. capensis meadows being under increased pressure from anthropogenic influences, it is important to establish which fish species and families utilize these habitats and what role they play in the ecology of fish assemblages within the Knysna Estuary. The primary objective of this study was to compare the use of Z. capensis and adjacent bare sediment areas by mainly large juvenile and subadult sparids and mugilids using different techniques. The two main hypotheses were as follows; 1) Mugilidae are likely to be more dominant in the unvegetated areas of the estuary littoral and Sparidae are likely to predominate within the Z. capensis bed areas of the estuary littoral. 2) The non-destructive underwater video monitoring method would yield similar fish composition data to seine netting sampling of the identical sites. Both hypotheses were assessed using data collected during this study and the analysis of historical unpublished data. Overall, Mugilidae were more abundant at bare unvegetated areas where they did most of their foraging. Sparidae were more abundant in the Z. capensis beds, which was also the habitat where they primarily foraged. With regards to the comparison of two different sampling methods, namely underwater video monitoring and seine netting, similar patterns arose with regards to the fish species observed in camera footage and those captured in the seine net, although the abundances were not always comparable.
Keywords: Gray mullets -- South Africa Knysna Lagoon; Sparidae -- South Africa Knysna Lagoon; Seagrasses -- South Africa Knysna Lagoon; Eelgrass -- South Africa Knysna Lagoon; Gray mullets Habitat -- South Africa Knysna Lagoon; Sparidae Habitat -- South Africa Knysna Lagoon; Underwater videography in wildlife monitoring; Seining; Zostera capensis Setchel